The Approach of the Constitutional Courts of the EU Member States to the Preliminary Ruling of the Court of Justice of the European Union - Ali Reza Jalali; Mohammad Abouata (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2019)
One of the legal tools used by the Court of Justice of the European Union in its jurisdictional system is the preliminary ruling on the basis of Article 267 of the Treaty on the Functioning of the European Union. According to this rule, the national courts can ask the Court to respond about the interpretation and correct way of applying a European law in a european country, with the aim of removing doubts and perplexities. This process ends with the enactment of a preliminary ruling by the Court. If the request for a preliminary ruling by the lower national courts is a consolidated fact, on the other hand the same can not be said for the requests of the Constitutional Courts, which have not reached a common view on the subject. In this article, in addition to the description of the cases of references for preliminary rulings of the Constitutional Courts of countries such as Italy, France, Spain and Germany before the Court of Justice of the European Union, we will try to understand the events concerning these referrals and mutual approaches held by the courts with particular attention to the approach of national Constitutional Courts.